Fast and Efficient Filter Using Wavelet Threshold for Removal of Gaussian Noise from MRI/CT Scanned Medical Images/Color Video Sequence. Issue 1 (2nd January 2022) - Elaiyaraja, G.; Kumaratharan, N.; Chandra Sekhar Rao, T.
Abstract : We proposed an optimum de-noising filter using wavelet threshold for the removal of adaptive white Gaussian noise from degraded medical images/colour video sequence based on system noise calculation. The performance of the proposed Gaussian de-noising technique is compared with various de-noising techniques such as Bayesian least squares-Gaussian scale mixtures, bilateral filter, adaptive bilateral filter, multi-resolution bilateral filter, nonlocal-Means, wavelet threshold based filters, and kernel-based method. The proposed methods have comparable/superior performance and less computational time compared to other techniques.